2019
DOI: 10.1093/mnras/stz1444
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out 3 keV warm dark matter using 21 cm EDGES data

Abstract: Weakly interacting cold dark matter (CDM) particles, which are otherwise extremely successful in explaining various cosmological observations, exhibit a number of problems on small scales. One possible way of solving these problems is to invoke (so-called) warm dark matter (WDM) particles with masses m x ∼ keV. Since the formation of structure is delayed in such WDM models, it is natural to expect that they can be constrained using observations related to the first stars, e.g., the 21 cm signal from cosmic daw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 73 publications
1
44
0
Order By: Relevance
“…For example, Baur et al (2016) found a lower limit of 2.96 keV from observations of the Lyman-alpha forest, while Palanque-Delabrouille et al (2020) placed a lower limit of 5.3 keV (a similar limit is found by Iršič et al (2017)). Chatterjee et al (2019) used high-redshift 21-cm data from EDGES to rule out WDM with m WDM < 3 keV. Note that our limit is less sensitive to details of baryonic physics than the others, because our analysis relies on the cumulative abundance of dark matter halos.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baur et al (2016) found a lower limit of 2.96 keV from observations of the Lyman-alpha forest, while Palanque-Delabrouille et al (2020) placed a lower limit of 5.3 keV (a similar limit is found by Iršič et al (2017)). Chatterjee et al (2019) used high-redshift 21-cm data from EDGES to rule out WDM with m WDM < 3 keV. Note that our limit is less sensitive to details of baryonic physics than the others, because our analysis relies on the cumulative abundance of dark matter halos.…”
Section: Discussionmentioning
confidence: 99%
“…Observational constraints are often reported in terms of the thermal WDM mass m WDM . The current strongest limits from Lyman-α forest data and redshifted 21 cm signals in EDGES observations [86] are, respectively, m WDM > 5.3 keV [40] and m WDM > 6.1 keV [44,45] (up to a galaxy formation model [46,47]). In the conventional thermal (or early decoupled) WDM model, the WDM temperature is determined such that the thermal relic abundance coincides with the observed DM mass density.…”
Section: Introductionmentioning
confidence: 91%
“…The recent measurement of the 21-cm absortion signal due to the light of the first stars, reported by the EDGES Collaboration [60], can provide lower bounds on the mass of non-cold dark matter candidates. If N 1 is mainly warm, this observation implies roughly m N 1 3 keV [61]. A rigorous approach to the implications of mixed DM in the structure formation may also put bounds on the parameter α [62,63].…”
Section: Jhep10(2021)005mentioning
confidence: 99%